Magnetic Resonance Imaging-Based Measurement of Hippocampal Volume in Posttraumatic Stress Disorder Related to Childhood Physical and Sexual Abuse—A Preliminary Report - Bremner, J. Douglas (1997)
We have previously reported smaller hippocampal volume and deficits in short-term memory in patients with combat-related posttraumatic stress disorder (PTSD) relative to comparison subjects. The purpose of this study was to compare hippocampal volume in adult survivors of childhood abuse to matched controls. Magnetic resonance imaging was used to measure volume of the hippocampus in adult survivors of childhood abuse (n = 17) and healthy subjects (n = 17) matched on a case-by-case basis for age, sex, race, handedness, years of education, body size, and years of alcohol abuse. All patients met criteria for PTSD secondary to childhood abuse. PTSD patients had a 12% smaller left hippocampal volume relative to the matched controls (p < .05), without smaller volumes of comparison regions (amygdala, caudate, and temporal lobe). The findings were significant after controlling for alcohol, age, and education, with multiple linear regression. These findings suggest that a decrease in left hippocampal volume is associated with abuse-related PTSD.